2012
DOI: 10.1111/j.1548-1387.2011.01195.x
|View full text |Cite
|
Sign up to set email alerts
|

Labors of Love: The Transformation of Care in the Non‐Medical Attendant Program at Walter Reed Army Medical Center

Abstract: In this paper, we explore the Non‐Medical Attendant program at Walter Reed Army Medical Center in Washington, DC, which subsidizes the presence of war‐injured soldiers' family members as they live for months or even years at Walter Reed during treatment and rehabilitation. We elaborate the ambiguities of the program and draw on ethnographic research to demonstrate how the program's vagaries combine with the context of an overburdened military medical system and the more familiar strains of family caregiving to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 22 publications
(10 reference statements)
0
16
0
Order By: Relevance
“…Partly in reaction to the disastrously ill‐equipped landscape of rehabilitation that faced casualties of the Vietnam war, Walter Reed had robust rehabilitation programs and a sophisticated amputee clinic (Messinger 2010), and soldiers could, in theory, stay for as long as was needed to stabilize their body in its new form. The decision about how long to stay involved complex negotiations between soldiers and clinicians, and between them and the family members who were paid to live with soldiers throughout their rehabilitation (Wool and Messinger 2012). The Army Medical Command continually updated its practices and facilities as the landscape of injuries became clearer and as their own research and experience suggested new best practices.…”
Section: Innovation and Iatrogenisismentioning
confidence: 99%
“…Partly in reaction to the disastrously ill‐equipped landscape of rehabilitation that faced casualties of the Vietnam war, Walter Reed had robust rehabilitation programs and a sophisticated amputee clinic (Messinger 2010), and soldiers could, in theory, stay for as long as was needed to stabilize their body in its new form. The decision about how long to stay involved complex negotiations between soldiers and clinicians, and between them and the family members who were paid to live with soldiers throughout their rehabilitation (Wool and Messinger 2012). The Army Medical Command continually updated its practices and facilities as the landscape of injuries became clearer and as their own research and experience suggested new best practices.…”
Section: Innovation and Iatrogenisismentioning
confidence: 99%
“…By scrutinizing the American soldier's formation and the affective entailments of the military body and psyche, we can gain key insights into the soldier's lifeworld within American nodes of power (Killshaw ; Lutz ; MacLeish ; Messinger ; Wool ; Wool and Messinger ). But in some cases such approaches to militarism can elide questions of imperialism and empire.…”
Section: Empire Affect and Mimetic Labormentioning
confidence: 99%
“…Recent anthropological research has focused on “care” as an important experience in various contexts including end‐of‐life home healthcare (Buch , ), veterans rehabilitation (Wool and Messinger ), tuberculosis, and suicide epidemics (Stevenson ), and amongst those whose lives are shaped by extreme disenfranchisement, poverty, humanitarian crises, drug addiction, and mental health issues (Garcia ; Han ; Ticktin ). What we learn from these studies is that despite the power of biomedical regimes, local logics, practices, and experience of healing are often tightly bound with frameworks of care and moral responsibility.…”
Section: Care Closeness and Dealing With Problemsmentioning
confidence: 99%